MENINGKATKAN AKTIVITAS, KETERAMPILAN BERPIKIR KRITIS MATEMATIS, DAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL DANDELION - Rahimah, Rahimah; Novitawati, Novitawati (Bajang Institute, 2023)
The assessment activities carried out were motivated by the lack of understanding of students' mathematical concepts when solving problems, the learning process was still one-way, and learning was less meaningful. The assessment process aims to improve teacher activity, student activity, mathematical critical thinking skills, and student learning outcomes using the DANDELION model. This study included the type of classroom action research through qualitative and quantitative approaches conducted in four meetings at SDN Berangas 1 in class V with a total of 15 students. Qualitative data were obtained from observations and interviews. Qualitative data were obtained from observations and interviews. Quantitative data are obtained from written tests both individually and in groups. In the study that occurred explained that teacher activities had been realized according to the learning model procedures to reach a score of 35 with very active criteria, student activity increased to reach a classical percentage of 93% with very active criteria, mathematical critical thinking skills increased to reach a classical percentage of 93% with very skilled criteria, and student learning outcomes continued to increase with a classical percentage of 100% until reaching success indicators